Infant formula feeding practices in a prospective population based study. Issue 1 (December 2016) - Smith, Hazel; Hourihane, Jonathan; Kenny, Louise; Kiely, Mairead; Leahy-Warren, Patricia; Murray, Deirdre
Abstract Background It is recommended that formula-fed infants are given standard whey-based infant formula throughout the first year of life, unless otherwise advised by healthcare professionals. To our knowledge it has not yet been explored if parents are using a whey-based infant formula throughout the first 12 months of life. Reasons for parental choice of formula are also unknown. Therefore, the objective of this paper was to describe parental administration of whey-based and non whey-based infant formula in the first year of life. Methods Data collected as part of the Cork BASELINE Birth Cohort Study examined infant feeding practices at 2, 6 and 12 months of age. Descriptive analysis explored infant feeding practices and parental reasons for changing from a whey-based to a non whey-based infant formula. Multiple logistic regression investigated parental and infant characteristics associated with the use of whey-based infant formula. Results In total, 62.4%, 40.4% and 12.8% parent(s) at 2, 6 and 12 months, respectively, gave their infant whey-based infant formula. No parental or infant characteristic was found to consistently influence the use of whey-based infant formula. The most common reason reported by parent(s) for changing their infant's formula to a non whey-based formula was that they perceived their baby as being hungry. Conclusion The majority of parent(s) commence their infants on whey-based formula, but most change to non whey-based formula before 12 months of age. Parental perception of infant satiety and not healthcare advice was the most common reason for changing from a whey-based to a non whey-based infant formula. Additional research is now required to investigate the effect of whey-based and non whey-based infant formula on infant growth.